Do Airports Boost Economic Development by Attracting Talent? An Empirical Investigation at the Subcounty Level1. (5th March 2017) - Chen, Xinxiang; Chi, Guanghua; Chi, Guangqing
Abstract : Objective: The objectives of this study were to examine (1) the linkage from airports to regional talent distribution and (2) the effect of talent on regional economic development. Methods: Using the data collected in Wisconsin at the municipal level, a subcounty level, in a region of the North Central United States from 1970 to 2010 and the American Community Survey 2006–2010 five‐year estimates, and random effects models and structural equation models, we employ descriptive and inferential statistics to examine the linkage from airports to talent to regional economic development. Results: We find that the farther a location is away from the airport, the lower its talent share tends to be, while greater passenger flow at the nearest airport increases a location's talent share. Given the quantity of passenger flow, a longer distance from the airport also reduces a location's talent share. The results furthermore suggest that economic development is impacted positively by passenger flow and talent share and negatively by distance to an airport. Conclusion: Our results underscore the intermediate role of talent between airports and regional economic development; building the linkage from airports to talent within the context of regional economic development provides important insights for local policy making aimed at attracting talented migrants.